Independent Curriculum in Learning at Madrasah Ibtidaiyah - Firmansyah, Muhamad Taufiq; Choirul Anam (Prodi PGMI STAI At-Tahdzib Ngoro Jombang, 2025)
This research aims to analyze the implementation process of the Independent Curriculum in learning at Madrasah Ibtidaiyah, identify supporting and inhibiting factors in its implementation, and evaluate the effectiveness of this curriculum in improving the quality of learning. The Independent Curriculum is an educational policy that provides flexibility for educational institutions and teachers to determine teaching methods and materials that suit the needs of students. This research uses a qualitative approach with a case study method at one Madrasah Ibtidaiyah that has implemented the Independent Curriculum. Data collection techniques were carried out through observation, interviews with the head of the madrasah and teachers, as well as document analysis related to the curriculum implementation. The results of the study show that the implementation of the Independent Curriculum in Madrasah Ibtidaiyah still faces various challenges, such as the readiness of educators, limited facilities and infrastructure, as well as the understanding of parents regarding curriculum changes. However, there are supporting factors such as flexibility in learning, increased teacher creativity, and support from the Ministry of Religious Affairs in the form of training and mentoring. The conclusion of this study indicates that the Independent Curriculum has a positive impact on learning in Madrasah Ibtidaiyah, especially in increasing students’ independence and creativity. However, improvements are needed in aspects of teacher training, strengthening infrastructure, and socializing with parents so that the implementation of this curriculum can run more optimally.